2016
DOI: 10.1371/journal.pone.0150741
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Rural Communities: Residents Living Near to Tembeling, Pahang and Muar Rivers, Malaysia

Abstract: The main aim of this study is to identify the quality of life (QoL) among communities residing near the Tembeling, Pahang and Muar Rivers in Malaysia. This quantitative study used a constructed questionnaire as main tool to collect data on the QoL of river communities. A total of 240 villagers were selected as respondents. The results indicated that the dimensions of settlement, safety, involvement and social relationships, as well as education scored highest, while dimensions of physical environment, financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…Several authors concur that QOL is one of the biggest challenges to government especially to reduce gap that exists between various groups and communities in the country (Idris et al, 2016). Meanwhile, other studies found quality of life has increased positively with improvement in environment, including physical and natural surroundings, education, health status, age, culture, safety as well as economic development level (Yassin et al, 2012;Skevington, 2010).…”
Section: Quality Of Life Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors concur that QOL is one of the biggest challenges to government especially to reduce gap that exists between various groups and communities in the country (Idris et al, 2016). Meanwhile, other studies found quality of life has increased positively with improvement in environment, including physical and natural surroundings, education, health status, age, culture, safety as well as economic development level (Yassin et al, 2012;Skevington, 2010).…”
Section: Quality Of Life Indicatorsmentioning
confidence: 99%
“…In Malaysia, numerous studies (Idris et al, 2016;Mohit, 2014; have been conducted to measure the QOL of the population. Several authors concur that QOL is one of the biggest challenges to government especially to reduce gap that exists between various groups and communities in the country (Idris et al, 2016).…”
Section: Quality Of Life Indicatorsmentioning
confidence: 99%
“…In Economics, it is the standard of living, in Medicine; it is the ratio of health and illness with the factors influencing healthy lifestyles. Idris, Shaffril, Yassin, Samah, Azimi and Samah (2016) postulated that a country is not rated as developed by its economic achievements and rapid progress but by the quality of life and well-being of its people. Idris et al (2016) further clarifies that there exists objective and subjective quality of life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Idris, Shaffril, Yassin, Samah, Azimi and Samah (2016) postulated that a country is not rated as developed by its economic achievements and rapid progress but by the quality of life and well-being of its people. Idris et al (2016) further clarifies that there exists objective and subjective quality of life. The objective quality of life in their opinion reveals itself in a person"s ability to adapt to the values of a culture and describes little about that person"s life such as social status and symbols which make one to be a member of that culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quality of life has a different meaning for every individual, as every person has his or her own set of expectations. Contexts in which people live, by one's values, and one's personal goals in life [1][2][3][4], as well as resilience in coping with stressful situations steer these expectations. Additionally, to a large extent, quality of life as a concept is subjective and multidimensional.…”
mentioning
confidence: 99%